Transcriptional Expression of Escherichia coli Glutamate-Dependent Acid Resistance Genes gadA and gadBC in an hns rpoS Mutant - Waterman, Scott R. (American Society for Microbiology, 2003)
Resistance to being killed by acidic environments with pH values lower than 3 is an important feature of both pathogenic and nonpathogenic Escherichia coli. The most potent E. coli acid resistance system utilizes two isoforms of glutamate decarboxylase encoded by gadA and gadB and a putative glutamate:γ-aminobutyric acid antiporter encoded by gadC. The gad system is controlled by two repressors (H-NS and CRP), one activator (GadX), one repressor-activator (GadW), and two sigma factors (σ(S) and σ(70)). In contrast to results of previous reports, we demonstrate that gad transcription can be detected in an hns rpoS mutant strain of E. coli K-12, indicating that gad promoters can be initiated by σ(70) in the absence of H-NS.